Análise fisiológica, bioquímica e proteômica das respostas ao estresse salino em plantas enxertadas de cajueiro anão precoce (Anacardium occidentale l.) - Amaral, Nathália Dias de Oliveira (2016)
This study aimed to investigate the physiological and biochemical responses and elaborate a protein profile of leaves of dwarf cashew plants (Anacardium occidentale L.) subjected to salt stress. Four scion/rootstock combinations (CCP 06/CCP 06, CCP 06/BRS 265, BRS 265/CCP 06 and BRS 265/BRS 265) were grown in plastic pots with 7.0 L of soil. The plants were irrigated by using water with electric conductivity (ECw) of 0.8 (control), 2.0 and 4.0 dS m-1. After 60 days of treatment, we analyzed the variables of growth (leaf area, dry mass, and scion and rootstock diameter), physiologic (gas exchange, water relative content, SPAD index and chlorophyll fluorescence) and biochemical (antioxidant enzymes, organic and inorganic solutes, and leaf protein profile), as well as identified e characterized the salt-stress responsive proteins. In general, the data clearly showed that BRS 265/CCP 06 plants were less affected by salinity, whereas CCP 06/CCP 06 plants were the most injured by salt stress. Salinity significantly decreased the chlorophyll relative content in all scion/rootstocks combinations, with the more conspicuous effects at 4.0 dS m-1 in CCP 06/CCP 06 and CCP 06/BRS 265 plants. In addition, the highest chlorophyll content values were detected in the BRS 265/CCP 06 plants. The higher and lower salt tolerance of BRS 265/CCP 06 and CCP 06/CCP 06, respectively, was correlated with alterations in the photosynthesis, transpiration, stomatal conductance and Rubisco carboxylation efficiency. The photosystem II quantic efficiency was reduced by 4.0 dS m-1 salinity, irrespective of scion/rootstock treatment, as compared to control. Under salinity, a better performance of photosystem II was found in BRS 265/CCP 06 plants which was concordant with the better photosynthetic and growth rates. The leaf superoxide dismutase (SOD) activity was little altered by studied treatments. On the other hand, in roots, salt stress severely decreased the SOD activity, especially at 4.0 dS m-1, it being less evident in the BRS 265/CCP 06 and BRS 265/BRS 265 combinations. The activity of ascorbate peroxidase (APX) in the leaves was significantly reduced by salinity in different scion/rootstocks treatments; however, under irrigation with saline water, the biggest APX activity was registered in the plants BRS 265/CCP 06 and BRS 265/BRS 265. In roots, a similar response was observed, except for salt-stressed BRS 265/BRS 265 plants, which showed APX activity higher than the control. Interestingly, guaiacol peroxidase (GPX) activity was detected only in roots and it was improved by salinity, except for BRS 265/BRS 265 plants. The Cl- content improved by increasing the salts in the water irrigation, regardless the plant organ and scion/rootstock combination. At 4.0 dS m-1, CCP 06/CCP 06 plants exhibited a massive accumulation of Cl- in the leaves, showing the highest values of this ion as compared by other treatments. The K+ concentrations significantly vary as affected by all analyzed treatments, except for leaves of BRS 265/BRS 265 combination. Reductions in leaf K+ content by salinity in the irrigation water were detected only in BRS 265/CCP 06 plants. In contrast, at salinity of 4.0 dS m-1, CCP 06/CCP 06 and CCP 06/BRS 265 plants showed K+ content 35 and 84% higher than the control plants, respectively. In roots and stems, all scion/rootstock combinations had their K+ content decreased by salt stress, regardless of CE in the irrigation water. In presence of salinity, Na+ content increased in all plant organs, irrespective of scion/rootstock treatment. Nonetheless, the highest improvements were registered in the leaves, where BRS 265/BRS 265, BRS 265/CCP 06 and CCP 06/BRS 265 plants exhibited Na+ content values 248, 269 and 456% bigger than the respective controls. Surprisingly, the Na+ content in salt-stressed CCP 06/CCP 06 plants was 650% higher than the control. Although the leaf Na+/K+ ratio had showed similar enhancement at 2.0 and 4.0 dS m-1 in both CCP 06/CCP 06 and CCP 06/BRS 265 treatments, it was increased with the increment of salinity in the irrigation water in BRS 265/CCP 06 and BRS 265/BRS 265 combinations. In stems, the Na+/K+ ratio drastically increased in high-salt stressed plants (4.0 dS m-1), with values found in BRS 265/CCP 06 combination 350% greater than the control; whereas in roots, these plants showed the lowest values of this ratio, suggesting a Na+ preferential accumulation mechanism in the stem. Carbohydrate content was little or not altered by salinity. Conversely, proline and free amino acids contents strongly increased in leaves and stems, mainly at 4.0 dS m-1 in BRS 265/CCP 06 and BRS 265/BRS 265 plants; and their content differentially change in roots as affected by scion/rootstock treatment. Whereas the proline content improved in CCP 06/BRS 265 and BRS 265/CCP 06 plants, the free amino acids increased exclusively in CCP 06/CCP 06 and BRS 265/CCP 06 ones. Salt stress differentially altered the expression of several proteins, as well as promoted de novo synthesis and deletion of some proteins. Herein, proteomic characterisation by two-dimensional gel electrophoresis (2DE) showed 347 differentially expressed spots (p value < 0.05 and intensity % > 1.4-fold) by both salinity and scion/rootstock treatments. A total of 151 spots were analyzed by LC-ESI-MS/MS, but only 128 proteins (85%) were identified and 23 (15%) were not found in protein data banks. The identification of these spots indicated that the major groups of differential proteins were associated with photosynthetic metabolism (27.3%), reserve/energy metabolism (25%), response to stresses (13.3%), carbohydrate metabolism (10.2%), secondary metabolism (7.0%), amino acids metabolism (7.0%), energy metabolism (5.5%), antioxidant metabolism (3.1%) and structural (1.6%). Our research evidences the impact of physiological and biochemical studies combined with proteomic approach, revealing an efficient strategy to elucidate the mechanisms of salt stress acclimation/tolerance. In conclusion, our data suggest that the combination of BRS 265 (as scion) and CCP 06 (as rootstock) is more advantageous for the growth of dwarf cashew plants under salt stress.